Antioxidant, Anti-inflammatory, and Anticoagulation Properties of Aegiceras corniculatum and Acanthus ilicifolius - Rana Biswas; S. M. Mahbubur Rahman; Kazi Mohammed Didarul Islam; Md. Morsaline Billah; Afiya Aunjum; Tauhidur Rahman Nurunnabi; Sujan Kumar Kundu; Md. Emdadul Islam (Mazandaran University of Medical Sciences, 2019)
Free radical production from different biological and environmental sources is due to an imbalance of natural antioxidants, which further leads to inflammation. Antioxidant metabolites are often characterized by anti-inflammatory and anticoagulation activity. Mangrove plants synthesize different classes of metabolites, including antioxidants, to minimize the devastating effect of oxidation resulting from the elevated salinity, UV, and other unique geochemical components. Accordingly, this study aimed at investigating the antioxidant, anti-inflammatory, and anticoagulation properties, as well as polyphenol content of the two selected mangrove plant species: Aegiceras corniculatum and Acanthus ilicifolius. We used the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, reducing power, ferric reducing antioxidant power (FRAP) assay, β-carotene-linoleic acid bleaching assay (BCB), total phenolic content (TPC), total flavonoid  content (TFC) and total tannin content (TTC) to determine antioxidant activity of the ethanol extract of A. corniculatum bark and leaves and A. ilicifolius leaves. Furthermore, human red blood cell (HRBC) membrane stabilization assay, lipoxygenase (LOX) inhibition assay, and prothrombin time (PT) test were performed for determining anti-inflammatory activity of the samples. A. corniculatum bark is a potent antioxidant (IC50 20.49 ± 2.14 µg/mL in DPPH assay) with anti-inflammatory (IC50 23.58 ± 1.75 µg/mL in LOX inhibition assay) and anticoagulation activity (18.19 ± 0.13 min in prothrombin time assay) compared to other extracts. All extracts were found with significant (P<0.001) antioxidant, anti-inflammatory, and anticoagulation properties. Further studies on liquid chromatography-mass spectrometry (LC-MS) analysis, anti-inflammatory, and anticoagulation are recommended.